(untitled) (Bangladesh Journal of Zoology, 2019)
Attempt has been taken to develop intensive tank culture technique providing natural environment for Stinging catfish (Heteropneustes fossilis) inside tank to increase survival rate as well as production. The experiment was conducted for a period of 150 days in two tanks (T1 and T2) of 300 m2. Fish fries with a mean weight and length ranged from 1.02 to 2.2 g and 2.7 to 3.5 cm were stocked in T1 and T2, respectively. Stocking density of fingerlings were 1, 25,000 and 1, 50,000 per Ha in T1 and T2, respectively. Commercial pelleted feed was supplied to tank reared fish twice daily at a rate of 3-10% of body weight per day and later feeding rate was adjusted based on body weight by sampling. Important water quality parameters (temperature, DO, pH, transparency, ammonia and nitrate) were recorded weekly throughout the culture period. Survival rate was 87% and 84% in T1 and T2, respectively. Mean final weight were 41.73 ± 2.09g and 40.6 ± 0.90 g in T1 and T2, respectively. Length-weight relationship indicates that the growth rate was always higher in T1 followed by T2. Results showed that net yield was relatively higher in T2 (5115.35 ± 113.13 Kg/ha) than T1 (4537.12 ± 227.4 Kg/ha). In case of production, there was significant difference (p < 0.05) between two treatments. This experiment demonstrated the potential of H. fossilis production through new technique of tank culture system. However, more research is needed using local feed ingredients with higher stocking density. Bangladesh J. Zool. 47(1): 107-119, 2019